Improving Speaking Ability through Student Role Playing Methods Class B Kindergarten Irene Tondano - Fenny N. Pusung; Donal Matheos Ratu; Viktory Nicodemus Joufree Rotty (AIBPM Publisher, 2020)
The purpose of this study is to Improve Speaking Ability through the Role-Playing Method of Class B Kindergarten Students Irene Tondano. This research was conducted in Irene Class B Kindergarten. Based on the results of research and discussion, it can be stated that the role-playing method can improve speaking skills in Bre Ireine Tondano class students. The role-playing method can develop motor skills previously diagnosed so that this activity is beneficial for students' motor development. Complete learning outcomes in this study were obtained from the percentage obtained by students in Cycle I by 80.0%, in Cycle II by 93.3%, and in Cycle III by 96.6%. These results show an increase and achievement of the expected learning completeness. In learning Indonesian, especially before learning activities using the role-playing method, teachers must pay attention and consider the advantages and disadvantages of this method.